PROPOSED IMPROVEMENT FOR DISASTER MANAGEMENT FRAMEWORK IN CONDUCTING EMERGENCY RESPONSE PROJECT IN INDONESIA (CASE STUDY OF WAHANA VISI INDONESIA) (The Indonesian Journal of Business Administration, 2021)
Indonesia is located at the meeting points of three tectonic plates, which leads to higher risk of natural disaster occurrence. Based on data from National Disaster Mitigation Academy (BNPB), the number of natural disasters increased significantly from 2010 until 2020. Natural disaster causes casualties, injured people, damaged infrastructures, and will affect a lot of lives significantly. This is where emergency response takes the most important role to restore and recover the lives of victims. Emergency response is a part of disaster management process, which involves preparation and mitigation phase to make the process effective and efficient. WVI is a non-profit organization, which also perform emergency response in many natural disasters in Indonesia since 1998. WVI’s emergency response for Lombok earthquake in July – August 2018 (Lombok Earthquake Emergency Response project) is selected as subject of this research. WVI performed several programs in LEER project such as distribution of non-food item (NFI) program and water sanitation and hygiene (WASH) program. Based on interview with the first team leader of LEER project, there was delay in procuring and delivering the aid materials in the emergency program. The team leader mentioned that based on his experience, the delay reached until 2 weeks for the procurement for WASH program. After analyzing the root cause using Fish Bone Diagram, the delay was caused by several factors, but mainly due to lack of man competency and lack of procurement system. The lack of man competency was about the staff assigned in disaster area which didn’t have the logistic and warehousing competencies and experience. As for the lack of procurement system, although WVI already has vendor database, but it still hasn’t had the vendor category and area mapping, which enable staff in disaster area to quickly procure the aid material needed. In the case of LEER, WVI had to procure materials from Jakarta and Surabaya due to local vendors evacuated themselves, which finally caused more time and cost to be spent.As the solution for the root causes, the researcher proposed the creation of WVI Emergency Supplier Network (ESN) to address the lack of procurement system, which will enable WVI to have broad coverage of vendor and material alternatives from each province in Indonesia. ESN will help WVI to quickly locate the nearest vendor to the disaster area, and finally help the procurement process to be quicker. For the lack of man competency, the creation of Emergency Response Handbook is proposed as solution, since it has a comprehensive and easy-to-understand guidelines for emergency response, especially the logistic and warehousing function. Both proposed solutions are hoped to strengthen the current preparedness of WVI disaster management, and finally produced better and faster emergency response. Keywords: disaster management, emergency response, preparedness